Playful, intra-active, "world"-traveling: A framework for teaching adults across national borders in feminist ways - Brigette A Herron (Adult Education Research Conference, 2017)
Using poststructural concepts of subjectivities, posthuman concepts of intra-activity, and Maria Lugones' playful "world"-traveling, this paper theorizes how adult educators might work in feminist ways across national borders.
Keywords: Adult Education Praxis; Feminism; Maria Lugones